Atom probe analysis of BaTiO3 enabled by metallic shielding. (May 2023) - Kim, Se-Ho; Shin, Kihyun; Zhou, Xuyang; Jung, Chanwon; Kim, Hyun You; Pedrazzini, Stella; Conroy, Michele; Henkelman, Graeme; Gault, Baptiste
Abstract: Atom probe tomography has been raising in prominence as a microscopy and microanalysis technique to gain sub-nanoscale information from technologically-relevant materials. However, the analysis of some functional ceramics, particularly perovskites, has remained challenging with extremely low yield and success rate. This seems particularly problematic for materials with high piezoelectric activity, which may be difficult to express at the low temperatures necessary for satisfactory atom probe analysis. Here, we demonstrate the analysis of commercial BaTiO3 particles embedded in a metallic matrix. Density-functional theory shows that a metallic coating prevents charge penetration of the electrostatic field, and thereby suppresses the associated volume change linked to the piezoelectric effect. Graphical abstract: Image, graphical abstract